The politics of human enhancement (a few observations by a historian of political thought) - Szlachta, Bogdan (Chrześcijaństwo-Świat-Polityka, 2025)
Regardless of the judgments about the end of the Anthropocene as a phase of the evolutionary development of life, which is soon to be replaced by a subsequent phase, perhaps dominated by “more highly evolved beings from the point of view of evolution” (with a question of whether life will be sustained?), there is much debate today concerning the human ‘enhancement’, perhaps as a means of increasing our chances of survival. The text discusses issues related to the understanding of the state and human nature, revealing the multitude of perspectives that determine the variety of avenues explored also by researchers who consider a wide range of issues, including not only biotechnological, but also political ones. The erosion of deontic ethics is one of the hallmarks of contemporary problems associated with the possible adoption of public policies aimed at ‘enhancing’ human beings, as well as establishment of legal norms and state agendas defining the rules of research pursued by scholars.